2021
DOI: 10.3390/molecules26092631
|View full text |Cite
|
Sign up to set email alerts
|

Nano Carbon Doped Polyacrylamide Gel Electrolytes for High Performance Supercapacitors

Abstract: Novel polyacrylamide gel electrolytes (PGEs) doped with nano carbons with enhanced electrochemical, thermal, and mechanical properties are presented. Carboxylated carbon nanotubes (fCNTs), graphene oxide sheets (GO), and the hybrid of fCNT/GO were embedded in the PGEs to serve as supercapacitor (SC) electrolytes. Thermal stability of the unmodified PGE increased with the addition of the nano carbons which led to lower capacitance degradation and longer cycling life of the SCs. The fCNT/GO-PGE showed the best t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…CNTs dispersions can be used for many applications, such as lubricants [ 40 , 41 , 42 ], polymer nanocomposites [ 43 ], and more recently it has been drawing the attention of the scientific community for the development of next-generation porous solid-state electrolytes [ 44 , 45 , 46 , 47 ] and as electrode materials [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…CNTs dispersions can be used for many applications, such as lubricants [ 40 , 41 , 42 ], polymer nanocomposites [ 43 ], and more recently it has been drawing the attention of the scientific community for the development of next-generation porous solid-state electrolytes [ 44 , 45 , 46 , 47 ] and as electrode materials [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Except for APAM/poloxamer (Figure S7), the G' values of the other blends were consistently greater than G" over the entire range, indicating the elastic properties of the hydrogels [35]. In addition, it can also be found that the G' value of NPAM/poloxamer (135 Pa) was higher than that of CPAM/poloxamer (98 Pa), which means higher intensity [36,37]. The effect of temperature on the viscosity of the three composite systems was also investigated.…”
Section: Preparation and Characterization Of Materialsmentioning
confidence: 90%
“…The addition of nanocarbon material resulted in improved thermal stability and subsequently slower ageing of a polyacrylamide gel electrolyte [ 276 ].…”
Section: Countermeasuresmentioning
confidence: 99%